PENGARUH KONSELING KELOMPOK TERHADAP DISIPLIN BELAJAR SISWA KELAS X SMA NEGERI 14 PEKANBARU TAHUN AJARAN 2013/201 - Romaini, Romaini; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to see the effect of group counseling on the discipline of learning students class X SMA Negeri 14 Pekanbaru Academic Year 2013/2014. The method used is Quasi experiment with pattern on One group: One group pre test and post test design. This research using a sample of 10 students with Sampling Purposive sampling technique, group counseling is used as one way to improve student learning through discipline several times treatments. The hypothesis presented in this study is there is a difference in student learning discipline before and after group counseling service provided at level 5% error and a 95% confidence level. From the results of the processing of used test results of correlation of two variables retrieved group counseling activities that contribute to the improvement of student learning discipline of 45 %. Based on the results of data processing then it can be concluded that the group counseling activities well prepared asquite effective intervention techniques to enhance student learning in school discipline. Next searchers recommend to the supervisor teacher or counselor in order to carry out activities not only against the group counseling of students of class X but also to grade XI and XII in order to improve student learning discipline. Keywords: Counseling Group, Discipline Learning